Studies on the mycoflora of cold desert area of Himachal Pradesh - T.C. BHALLA; T.N. LAKHANPAL, ANAND SAGAR*, SMRITI RAGHWA (Indian Phytopathology, 2007)
The soil samples from rhizosphere of various plants of the cold desert areas of Himachal Pradesh were analysed for the presence of microorganisms. Forty five species of fungi including one species of Streptomyces were isolated from these soil samples. Of these isolates, twenty two species belonging to twelve genera fall in Deuteromycotina, eighteen species of fungi belonging to three genera fall in Ascomycotina and four species belonging to three genera fall in Zygomycotina. These fourty five isolates were characterised into psychrophiles, mesophiles and thermophiles. Twenty one species were found to be psychrophilic and seven were thermophilic and the remaining seventeen were psychrotolerant in nature.